PERANCANGAN SISTEM INFORMASI SMART CLUSTER BANDUNG - Titis Prasetyo (Computer Based Information System Journal, 2019)
The purpose of this study is to provide assistance to citizens in terms of correspondence between citizens and heads of citizens and discussion forums for citizens to interact with each other. Smart Cluster Bandung is an application that was created and developed by Universitas Komputer Indonesia students. Smart Cluster Bandung is a CSR (Corporate Social Responsibility) program as a form of the company's duties and responsibilities towards its social environment. In this case, the Bandung smart cluster makes the media to bridge between citizens and head of citizens. As well as a means of strengthening relations between citizens. Using this facility can be used as a place to stay in touch with local residents. In this study using a development system prototype. While the research method used is descriptive discussion by conducting interviews and observations. The results of this study provide positive results for residents in the cluster.